STRATEGI PEMBELAJARAN KETERAMPILAN MENULIS NARASI DENGAN TEKNIK URAI RUANG WAKTU (URW) DI KELAS III SEKOLAH DASAR - Saifudin, M.Fakhrur (Universitas Muhammadiyah Surakarta, 2015)
This study aims to describe the development strategy of the skill in writing a narrative text with theURW technique in the early Elementary School class. The research employed a descriptive-qualitativeapproach. It describes and analyzes the learning strategies of writing a narrative text with the URWtechniques. The data in this study included the actions and documents concerning the planning,implementation, and evaluation of learning. The data collection techniques used observation, interview,documentation, and questionnaires. The validity of the data employed a triangulation of data orsource. The data analysis applied an interactive model: data reduction, data display, and conclusion/ veriô€‚¿ cation. The analysis of quantitative data was used to determine the assessment of a narrativewriting skill with the URW techniques in the early primary school class. The results of this study showthat the URW techniques can be developed with a wide range, for example, the development of the Uraitechniques, the development of Time and Space techniques. The assessment of learning a narrativewriting skill with the URW techniques in class III of Primary Schools showed signiô€‚¿ cant improvement.This can be seen in the analysis of the data from three locations showing an increase. The highestincrease was in SD Muhammadiyah Pajangan at 92%, Muhammadiyah Senggotan at 88% and SDMuhammadiyah 3 Ambarketawang at 77%.